Wykorzystanie niektórych elementów leksykonu metatekstowego w kształceniu humanistycznym - Misztal, Barbara (Słowo. Studia językoznawcze, 2012)
The aim of the article is to signalize particular solutions dedicated to Polish humanities studies. Linguists as well as teachers note the problems in Polish education: the crisis of reading, learning and sentence building. The author points out the phenomena of edutainment and convergence culture in media. These occurrences cause that contemporary electronic generation perceives mainly pictures and uses them to communicate. The lack of contact with written language, i.e. the literature, causes the problem of understanding reading . The author proposes to use the Anglo-Saxon model of teaching creative writing in Polish language and gives the examples of Polish linking devices as an essential tool to create correct, clear and coherent texts.